Benchmark CFD validation data for surface combatant 5415 in PMM maneuvers – Part I: Force/moment/motion measurements. (15th November 2015) - Yoon, Hyunse; Simonsen, Claus D.; Benedetti, Lanfranco; Longo, Joseph; Toda, Yasuyuki; Stern, Frederick
Abstract: Part I of this two-part paper presents benchmark CFD validation force/moment/motion measurements for surface combatant 5415 in planar-motion-mechanism (PMM) maneuvers. The experiments are conducted in the IIHR towing tank as part of an international collaboration for development/application of uncertainty analysis procedures and assessment of scale effects and facility biases. Stationarity and normality tests and statistical convergence errors, single and multiple run methods for obtaining the maneuvering mathematical model hydrodynamic derivatives, and the effects of heave, pitch and roll motions and fixed/free mount conditions are assessed. Assessment of the methods for obtaining the hydrodynamic derivatives is based on reconstructions of the measured force and moment time histories. Part 2 presents phase-averaged stereo PIV flow field measurements. The data is used as a test case at the SIMMAN 2008 and 2014 workshops on verification and validation of ship maneuvering simulation methods. Highlights: Experimental data are provided for CFD ship maneuvering simulations validation. Data quality is assessed using statistical convergence and uncertainty analysis. Single- vs. multiple-run methods for hydrodynamic derivatives are compared. The effects of model size are assessed by comparing three facilities data. The effects of motions are assessed by comparing fixed- vs. free-model conditions.